Melatonin treatment protects against ischemia/reperfusion-induced functional and biochemical changes in rat urinary bladder - ŞENER, GÖKSEL; ELÇİOĞLU, HATİCE KÜBRA (My University, 2003)
Reactive oxygen metabolites play important roles in ischemia/reperfusion (I/R) injury in several systems. The aim of this study was to investigate the role of melatonin against I/R injury of the rat urinary bladder. The abdominal aorta was clamped to induce ischemia for 30 min, then the animals were subjected to 60 min of reperfusion. Melatonin (10 mg/kg, i.p.) or the vehicle (control 1% alcohol i.p.) was administered before I/R. After decapitation, the bladder was removed and the tissue was either used for functional studies or stored for measurement of products of lipid peroxidation (LP), glutathione (GSH) levels and myeloperoxidase activity (MPO). Bladder strips were suspended in oxygenated Tyrode's buffer at 37 degrees C and isometric contractions to carbachol (CCh; 10(-8)-10(-4) m) were recorded. In the I/R group, the contractile responses of the bladder strips were lower than those of the control group (P < 0.01-0.001) and were reversed by treatment with melatonin (P < 0.05-0.001). LP which was higher in I/R group compared with control (27.68 +/- 1.69 and 10.59 +/- 1.27 nmol/g, respectively; P < 0.001) was partially reversed by melatonin (19.01 +/- 1.85 nmol/g; P < 0.01). Similarly, GSH showed a decrease in the I/R group compared with controls (0.27 +/- 0.03 and 0.43 +/- 0.04 micromol/g, respectively; P < 0.05) and melatonin prevented this effect completely (0.45 +/- 0.04 micromol/g; P < 0.05). MPO activity in the I/R group (4.19 +/- 0.08 U/g) was significantly higher than that of the control group (1.41 +/- 0.08 U/g; P < 0.001) and melatonin treatment reduced MPO levels compared with I/R alone (3.16 +/- 0.07; P < 0.001). Melatonin almost completely reversed the low contractile responses of rat urinary bladder strips to CCh and prevented oxidative tissue damage following I/R.
Keywords: Animals; Male; Rats; Antioxidants; Melatonin; Glutathione; Lipid Peroxidation; Malondialdehyde; Oxidative Stress; Peroxidase; Reperfusion Injury; Rats, Sprague-Dawley; Urinary Bladder; Carbachol; Cholinergic Agonists; Muscle, Smooth; Muscle Contraction; Organ Culture Techniques